Cooperative core competencies in tourism: Combining resource-based and relational approaches in destination governance - Pechlaner, H.; Bachinger, M.; Volgger, Michael; Anzengruber-Fischer, E. (International University College, 2014)
Community-based tourist destinations can be understood as networks of tourism service providers, which need to combine their resources and competencies to generate the overall holiday experience. Building on strategic management theories, the study aims at exploring the relationship between the destinations management’s reflexive capabilities and the cooperative core competencies of a tourist destination. By means of reflexive capabilities, destination management is suggested to be able to induce a high level of network quality, which in turn may be a pre-condition for the interlacing of the service providers’ competencies and resources, i.e. for the development of cooperative core competencies. Based on a quantitative survey in Bavaria, the results support these assumptions and indicate that reflexive capabilities may promote the development of cooperative core competencies in tourist destinations. The paper advances tourism literature by introducing, operationalizing and testing the idea of cooperative core competencies in the context of tourist destinations.